2019
DOI: 10.1159/000494672
|View full text |Cite
|
Sign up to set email alerts
|

Microbleeds of Lacunar Infarction and Middle Cerebral Artery Flow Velocity of Branch Atheromatous Disease Are Essential Factors of Stroke Etiology

Abstract: Background: Although subcortical infarction patients sometimes show larger infarction size than the definition of small vessel occlusion (SVO), there are no specific predictors of larger size. The aim of this study was to identify the factors, including magnetic resonance imaging (MRI) and ultrasonographic parameters, to predict larger subcortical infarction. Methods: Consecutive patients with acute supratentorial subcortical infarction were studied. Patients were classified into 2 groups (L: larger group, ≥15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
(22 reference statements)
0
2
0
Order By: Relevance
“…In the baseline information study of different groups, the first three factors related to TOAST classification, atrial fibrillation, stroke history, and diabetes accounted for a very high proportion in group CE, especially atrial fibrillation, accounting for 33.06%, much higher than that in other groups, which was consistent with the results of previous studies, indicating the reliability of the research data. In clinical work, we routinely perform the TOAST of ACI patients to a certain extent to predict their prognosis [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…In the baseline information study of different groups, the first three factors related to TOAST classification, atrial fibrillation, stroke history, and diabetes accounted for a very high proportion in group CE, especially atrial fibrillation, accounting for 33.06%, much higher than that in other groups, which was consistent with the results of previous studies, indicating the reliability of the research data. In clinical work, we routinely perform the TOAST of ACI patients to a certain extent to predict their prognosis [17][18][19] .…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have shown that arterial wall morphology and plaque characteristics help distinguish the different mechanisms underlying stroke (10)(11)(12)(13). The remodeling pattern (positive or negative), distribution (superior, inferior, ventral or dorsal wall), plaque burden (PB), and vulnerability of intracranial plaque may be associated with the pathogenesis and disease process of different types of infarction (6,(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%